Developing Children's Expressive Language Through the Storytelling Methods - Baroroh, Millatul; Farida, Siti; Dianita, Evi Resti (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
This study analyzes the storytelling method's implementation in children's expressive language. The research method used is descriptive qualitative. Data collection techniques using observation, interviews, and documentation. Data analysis uses the steps proposed by Milles & Huberman, namely data reduction, data presentation, and conclusions. The results of this research are 1) the teacher implements the storytelling method following the stages of the lesson plan that has been prepared previously with storytelling techniques adapted to the story conveyed 2) The development of children's expressive language has increased.